Personalens blick på barns tillhörighet i förskolan - Johansson, Eva M. (Nordisk barnehageforskning, 2022)
Den här delstudien utforskar tillhörighet med utgångspunkt i personalens blick på barnens gemenskaper. Tillhörighet förstås som en upplevelse av att ”känna sig hemma”. Data består av gruppintervjuer med personal från tre förskolor i Norge. Följande frågor är aktuella: Hur ser barns gemenskaper ut utifrån de yrkesverksammas blick och vilka tillhörigheter menar de att barnen är en del av? Vilka villkor för barns tillhörigheter kan identifieras i de yrkesverksammas beskrivningar? Studiens teoretiska ramverk grundas i tillhörighetspolitik; en teori som har utvecklats av Nira Yuval-Davis (2011) och tar utgångspunkt i att sociala positioner, identifikationer och värden bidrar till att skapa villkor för tillhörighet i förskolan. Analysen visar att de yrkesverksamma identifierar en rad olika gemenskaper mellan barnen, vilka till stora delar baseras på likhet. I de yrkesverksammas förståelser av barns gemenskaper har spänningsfält utmejslats vilka har betydelse för de tillhörigheter som möjliggörs. Dessa spänningsfält handlar om gemenskaper som utmanar förskolegemenskapen i stort, samt frågor om anpassning, makt och konflikt som villkor för gemenskap. Utmaningen för de yrkesverksamma är att systematiskt utnyttja sin kunskap om barns gemenskaper och de villkor för tillhörighet som skapas och i det arbetet ta fasta på en pedagogik där de tillsammans med barn kan problematisera och förändra orättvisor och sociala strukturer som riskerar att hindra barns tillhörighet. English abstract Children’s communities from the perspective of the professional In this sub-study, children’s communities and belonging are explored from the educator’s point of view. Belonging is understood as a sense of “feeling at home”. In group interviews with educators from three preschools in Norway, following questions were addressed: What do children’s communities look like from the perspective of the professionals? What conditions for belonging can be identified in the educators’ descriptions? The theoretical framework of the study is founded in The Politics of Belonging, a theory developed by Nira Yuval-Davis (2011, 2015). This theory describes how different social conditions, such as social positions, emotional identifications, and values, affect how belonging is constructed and experienced by children and educators in preschool. The analyses showed how the educators identified a variety of children’s communities – mainly based on similarity. In the professionals’ understandings of children’s communities, fields of tension were identified, which in turn appeared important for belonging. The fields of tension identified were communities that challenge, close relationships, and common cultural traditions. Adaptation, power, and conflict were also identified as conditions for community.From this study, we learn that professionals embrace manifold knowledge about children’s communities and conditions for belonging in preschool. The challenge for educators is to utilize and critically relate to their rich knowledge, and to focus on a pedagogy that aims to involve children in problematizing, challenging, and changing injustices that may prevent children’s belonging in the future.